The Effect of GeoGebra-Assisted Problem-Based Learning on Junior High School Students' Mathematical Problem-Solving Skills - Adetia Pratama; Siti Aminah; Lee Ngan Hoe (Gema Cendekia Institute, 2026)
Mathematical problem-solving ability is one of the essential competencies required for students in the 21st century. However, various educational evaluations indicate that Indonesian junior high school students still demonstrate relatively low problem-solving skills. One promising instructional approach to address this issue is the implementation of GeoGebra-assisted Problem-Based Learning (PBL). This study aimed to investigate the effect of GeoGebra-assisted Problem-Based Learning on junior high school students' mathematical problem-solving ability. A quantitative approach with a quasi-experimental design using a pretest-posttest control group design was employed. The sample consisted of 64 eighth-grade students divided into experimental and control groups. Data were collected through mathematical problem-solving tests and analyzed using descriptive statistics and independent sample t-tests. The findings revealed that students who participated in GeoGebra-assisted Problem-Based Learning demonstrated significantly higher improvements in mathematical problem-solving ability than those receiving conventional instruction. These results support previous studies highlighting the effectiveness of integrating GeoGebra into problem-based learning environments. Therefore, GeoGebra-assisted Problem-Based Learning can be recommended as an effective instructional alternative for enhancing junior high school students’ mathematical problem-solving ability.